Promoção da Saúde Mental nas Escolas – Projeto ES´COOL - Tomé, Gina (2019)
The ES’COOL Project arises because of the gap in the promotion of mental health in a school context, especially in the training of teachers. The main goal of “ES´COOL” is to promote adolescents’ mental health through capacity building of school teachers and school staff. The program aims the development of personal and social skills, and includes the prevention of anxiety and depression symptoms and the promotion of resiliency, and self-regulation in adolescents. The training aims to enable effective referral and early intervention in complex situations and promote dialogue with parents and school staff about mental health. The project will occur in three phases and will include teachers from primary and secondary schools (from 1st to 12th grade), kindergarten teachers and special education teachers covering schools from all the regions of Portugal. With the ES’COOL training, it is intended to create in schools a cycle that generates projects promoting well-being and mental health in Portuguese adolescents.